Carbon nanotube modified sodium dodecyl sulfate antistatic agent, preparation method thereof and polyurea composite material

By combining carbon nanotubes with sodium dodecyl sulfonate, a modified antistatic agent was prepared and combined with polyurea materials, the problem of insufficient effects of traditional antistatic agents in complex scenarios is solved, and the efficient antistatic and comprehensive performance improvement of polyurea materials is achieved.

CN119614002AInactive Publication Date: 2025-03-14SHENYANG JUSHENG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510153705.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional sodium dodecyl sulfonate antistatic agents lack antistatic effects and surfactivity in complex use scenarios, and the comprehensive performance declines after adding other components to polyurea coatings.

Method used

By combining carbon nanotubes with sodium dodecyl sulfonate and designing a reasonable ratio, a carbon nanotube modified sodium dodecyl sulfonate antistatic agent was prepared, and combined with polyurea material to form a composite material.

Benefits of technology

It significantly improves the antistatic effect of polyurea materials, and to a certain extent, its bonding strength, shear strength and other properties are improved. The preparation method is simple and suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614002A_ABST
    Figure CN119614002A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube modified sodium dodecyl sulfate antistatic agent, a preparation method thereof and a polyurea composite material, and belongs to the technical field of polyurea materials. The carbon nanotube modified sodium dodecyl sulfate antistatic agent comprises a carbon nanotube (CNTs) mixture and a sodium dodecyl sulfate mixture, and the two materials are activated, modified and reasonably proportioned, so that the performance of a composite material can be regulated and controlled. The carbon nanotube modified sodium dodecyl sulfate antistatic agent prepared by the method solves the problem of poor antistatic effect of a polyurea material, and improves the bonding strength, shear strength and other properties of the polyurea material to a certain extent. The prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is simple in preparation method, excellent in antistatic property and comprehensive mechanical property, capable of achieving multiple purposes, and particularly wide in application prospect in the field with high static electricity requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurea materials, and in particular relates to a carbon nanotube-modified sodium dodecyl sulfate antistatic agent and a preparation method thereof, and a polyurea composite material. Background Art

[0002] In the development of modern science and technology, polymer materials have received more and more attention. Nowadays, they have been widely used in aerospace, automobile manufacturing, construction engineering and electronic equipment, which have high requirements for comprehensive material performance. Among them, sodium dodecyl sulfate has also been widely used as an antistatic agent.

[0003] Sodium dodecyl sulfate is an anionic surfactant. In the molecular structure, there is a strongly hydrophilic sulfonic acid group connected to a hydrocarbon group, which has the advantages of strong surface activity, good solubility in low-temperature water, and excellent antistatic effect. However, with the advancement of science and technology, the antistatic ability and surface activity of traditional sodium dodecyl sulfate cannot meet the use requirements of more complex usage scenarios. Therefore, the antistatic properties of polyurea coatings are improved by modifying sodium dodecyl sulfate. The modification of sodium dodecyl sulfate is usually achieved by combining it with functional materials to achieve the performance and requirements that need to be met, but due to the addition of other components, it often leads to a decrease in the overall performance of polyurea coatings after it is added to the polyurea component.

[0004] Carbon nanotubes, also known as buckytubes, are one-dimensional quantum materials with a special structure. Their radial dimensions are in the nanometer range, their axial dimensions are in the micrometer range, and both ends of the tubes are basically sealed. Due to their unique structure and excellent electrical and chemical properties, they present broad application prospects and have attracted much attention in the fields of materials, physics, electronics, and chemistry. Carbon nanotubes are now mostly used to prepare many composite materials with excellent performance. For example, plastics reinforced with carbon nanotube materials have excellent mechanical properties, corrosion resistance, and radio wave shielding. Due to their good dispersibility and mechanical properties, carbon nanotubes can avoid the reduction of mechanical properties caused by adding other substances to the polyurea system.

[0005] In summary, the development of a polyurea protective coating that has the dual material properties of sodium dodecyl sulfate and carbon nanotubes, a simple synthesis process, excellent mechanical properties, and good antistatic effect has become an urgent problem to be solved. Summary of the invention

[0006] Based on the problems faced by the above-mentioned application fields, the present invention proposes a carbon nanotube-modified sodium dodecyl sulfate antistatic agent and its preparation method and polyurea composite material. Since sodium dodecyl sulfate contains sulfonic acid group and dodecyl group, it has excellent surface activity and peptization. It can form a microcolloid solution or emulsion in the solution, so that the interfacial tension of the solution is reduced, and the solute molecules are more easily dissolved or dispersed. Due to its high specific strength, carbon nanotubes can improve good mechanical properties for polyurea coatings. By designing a reasonable ratio of the two materials, the performance regulation of the composite material can be achieved. The carbon nanotube-modified sodium dodecyl sulfate antistatic agent prepared by the method solves the problem of poor antistatic effect of polyurea materials and improves its bonding strength, shear strength and other properties to a certain extent. In addition, the preparation method of the prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material is simple, and the prepared polyurea composite material has excellent performance in antistatic and comprehensive mechanical properties, and can achieve multiple uses of one material, especially in the field with high requirements for static electricity, and has a wider application prospect.

[0007] The present invention provides a method for preparing a carbon nanotube-modified sodium dodecyl sulfate antistatic agent, comprising the following steps: S1: Preparation of carbon nanotubes (CNTs) mixture Mix carbon nanotubes (CNTs) and potassium hydroxide particles (KOH), use distilled water as a solvent, stir to react evenly, dry, and cool to room temperature to obtain a carbon nanotube (CNTs) mixture; S2: Preparation of sodium dodecyl sulfate mixture (1) mixing the sufficiently cooled glacial acetic acid and chlorosulfonic acid uniformly, adding dodecanol, and stirring thoroughly until the dodecanol is completely dissolved to obtain a primary product of sodium dodecyl sulfonate; (2) placing the initial product of sodium dodecyl sulfate at low temperature, stirring it evenly with n-butanol, and slowly adding a saturated sodium carbonate aqueous solution to obtain a sodium dodecyl sulfate mixture; S3: Preparation of carbon nanotube modified sodium dodecyl sulfate antistatic agent The carbon nanotube (CNTs) mixture and the sodium dodecyl sulfate mixture are placed in an ice-water mixture, fully stirred to obtain a carbon nanotube-modified sodium dodecyl sulfate antistatic agent, and then cooled to room temperature.

[0008] In the step S1, the mass ratio of carbon nanotubes (CNTs): KOH is 1:(5-15).

[0009] In the step S1, the amount of distilled water used is based on the amount that can fully disperse the carbon nanotubes (CNTs) and KOH.

[0010] In the step S1, the stirring rate for uniform stirring reaction is 100-200 r / min, and the stirring time is 1-2 h.

[0011] In step S2 (1), the molar ratio of glacial acetic acid: chlorosulfonic acid: dodecanol is (2-3): 1: (1-2), and the preferred molar ratio is 2.2: 1: 1.9.

[0012] In step S2 (1), the powder particle size of dodecanol is 60-90 nm.

[0013] In step S2 (2), the low-temperature reaction is carried out in an ice-water mixture.

[0014] In step S2 (2), the molar ratio of sodium dodecyl sulfate initial product: n-butanol: saturated sodium carbonate solution is (50-55): (105-110): 1, and the preferred molar ratio is 52:109:1.

[0015] In step S2 (3), the purpose of slowly adding is to control the reaction rate and prevent agglomeration caused by excessive reaction. The speed of slowly adding is controlled to be 0.5-1.0 mL / min.

[0016] In the step S3, the mass ratio of carbon nanotubes (CNTs) to sodium dodecyl sulfate is (2-3):(1-2); preferably 2.3:1.5.

[0017] The carbon nanotube-modified sodium dodecyl sulfate antistatic agent of the present invention is prepared by adopting the preparation method.

[0018] The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention comprises the carbon nanotube-modified sodium dodecyl sulfate antistatic agent and polyurea material.

[0019] The preparation method of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention comprises the following steps: The PUA polyurea is preheated, and after being fully preheated, it is cooled to room temperature. With stirring, the carbon nanotube-modified sodium dodecyl sulfate antistatic agent is slowly added to the PUA polyurea, and after stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material is obtained.

[0020] In the preparation method of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the purpose of slowness is to make the carbon nanotube-modified sodium dodecyl sulfate antistatic agent disperse more evenly.

[0021] In the preparation method of the carbon nanotube modified sodium dodecyl sulfate-polyurea composite material, the preheating temperature is 70-80° C. and the preheating time is 10-20 minutes.

[0022] In the preparation method of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the added mass ratio of PUA polyurea and carbon nanotube-modified sodium dodecyl sulfate antistatic agent depends on the completeness of the reaction, and the suitable ratio of the number average molecular weight of the polyurea side chain to the number average molecular weight of the carbon nanotube-modified sodium dodecyl sulfate antistatic agent is (1.22~18.85):1, and the preferred molar ratio is (1.22~6.37):1.

[0023] The carbon nanotube modified sodium dodecyl sulfonate-polyurea composite material of the invention is prepared by adopting the above preparation method.

[0024] The resistance range of the carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 3.85×10 7 ~6.85×10 8 ohms / hq, the tensile strength ranges from 31MPa to 52MPa, the elongation at break ranges from 436% to 841%, and the impact strength can be increased by 76% to 116% compared with pure aluminum sheets. Under primer-free conditions, the adhesion to carbon steel can reach 7 to 11MPa.

[0025] The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention is used as a protective coating, especially for oil pipelines of aircraft and ships, to avoid fire accidents caused by frictional static electricity.

[0026] Compared with the existing polyurea coating and silicone rubber / polyurea coating, the carbon nanotube-modified sodium dodecyl sulfate antistatic agent and its preparation method and polyurea composite material of the present invention have the following advantages: 1. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention greatly enhances the antistatic effect of the polyurea material by adding the carbon nanotube-modified sodium dodecyl sulfate antistatic agent, and the added antistatic agent is controllable. The prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material can be applied to more application scenarios.

[0027] 2. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention significantly improves the antistatic ability of the polyurea coating, and the comprehensive performance of the material is also significantly improved compared with the known polyurea coating and silicone rubber / polyurea coating.

[0028] 3. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material of the present invention can be applied to oil pipelines of aircraft and ships to avoid fire accidents caused by friction static electricity.

[0029] 4. The present invention modifies carbon nanotubes by adding alkali to form carbon nanotube alcohol, which can increase the hydrophilicity of carbon nanotubes and improve the dispersibility of carbon nanotubes and aqueous phase substances. The sodium dodecyl sulfate mixture is configured to improve the surface charge characteristics of carbon nanotubes. Through these modification methods, the stability and dispersibility of carbon nanotubes in solutions are significantly improved, thereby enhancing their performance in various composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The graph is a graph showing the ratio of the amount of carbon nanotubes added to the amount of sodium dodecyl sulfate added and the surface resistance change in an embodiment of the present invention.

[0031] Figure 2 The graph is a variation curve of the ratio of the amount of carbon nanotubes added to the amount of sodium dodecyl sulfate added, and the tensile strength and elongation at break in the embodiment of the present invention.

[0032] Figure 3 This is a relationship diagram between the ratio of the amount of carbon nanotubes added to the amount of sodium dodecyl sulfate added and the material adhesion in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0034] In the following examples, the antistatic properties and mechanical properties of the prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material were tested, including the following testing work: (1) The prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material needs to be cured at a temperature of 25° C. to 30° C. for 2 to 3 days to achieve complete curing; (2) The antistatic performance test was conducted using a surface resistance tester (RT1000) from Dongguan Tongrong Antistatic Technology Co., Ltd. The test was conducted at an environment of 50~55%RH and 25~27℃; (3) Mechanical properties tests were conducted using a general tensile testing machine (GX-SF001) from Shenzhen Shared Instruments Co., Ltd. The test was conducted at a strain rate of 50 mm / min, and at least four samples were tested according to ISO 37-2005. The tensile specimen was 35 mm long, 2 mm wide in the middle, 1 mm thick, and had a gauge length of 10 mm; In the following examples, the antistatic performance test and mechanical performance test of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material include the following test work: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was cut into a rectangular sample of 10 cm × 15 cm, and placed on a polytetrafluoroethylene plate. The metal rod at the bottom of the electrostatic tester was placed flat on the surface of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material sample to perform an antistatic test. Among them, the thickness of the composite material sample is 1 to 1.5 mm.

[0035] In the following examples, the impact resistance test of the prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was carried out, including the following test work: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was cut into a rectangular sample of 10 mm × 30 mm, fixed on an aluminum alloy substrate of 100 mm × 12.5 mm × 1.5 mm with glue, and an impact test was performed on the composite structure consisting of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material sample and the aluminum alloy substrate using a paint film impact tester; Among them, the thickness of the composite material sample is 1-1.5mm; the impact speed of the impact test setting is 3.8m / s, and the hammer body is a simply supported beam 25J; In the following examples, the adhesion test of the prepared carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material to a carbon steel substrate includes the following test work: Adhesion test was performed using a pull-off adhesion tester (PosiTector® AT) from DeFelsko, USA. At least four samples were tested according to ASTM D4541. Before testing, ensure that the coating surface on the substrate is clean and free of contamination; stick a suitable size of ingot on the coating surface with a suitable adhesive to ensure that the adhesive is fully cured; record the maximum tensile force when the coating is separated, and observe and record the separation mode (such as coating self-destruction, separation of the coating and substrate interface, substrate damage, etc.).

[0036] Example 1 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was performed at a rate of 180r / min for 1.5h. After stirring evenly, the mixture was placed in a drying oven for drying. After drying, the mixture was cooled to room temperature for use; Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of an extremely fine solid powder with a particle size of 60-90 nm to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the dodecanol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate initial product was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain a sodium dodecyl sulfate mixture; wherein, in a molar ratio, the sodium dodecyl sulfate initial product: n-butanol: saturated sodium carbonate solution = 53.2:106:1; Weigh 0.5 g of the stirred carbon nanotube (CNTs) mixture and 0.5 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain a carbon nanotube-modified sodium dodecyl sulfate antistatic agent, and cool them to room temperature for later use; 100g of PUA polyurea was preheated in an oven, taken out and cooled to room temperature after sufficient preheating, and the carbon nanotube-modified sodium dodecyl sulfate antistatic agent was slowly added to the stirred PUA, and after stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0037] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 3.85×10 7 ohms / hq; the tensile strength is 51.865MPa, the elongation at break is 840.233%, the impact strength is increased by 115.015% compared with pure aluminum sheet, and the adhesion to carbon steel is 10.797MP without primer.

[0038] Example 2 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was applied. After stirring evenly, the mixture was placed in a drying oven and dried. After drying, the mixture was cooled to room temperature for later use. Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain sodium dodecyl sulfate; wherein, in a molar ratio, the initial product of sodium dodecyl sulfate: n-butanol: saturated sodium carbonate solution = 53.2:106:1; Weigh 0.5 g of the stirred carbon nanotube (CNTs) mixture and 1 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cool them to room temperature for later use; 100g of PUA polyurea was placed in an oven for preheating. After sufficient preheating, it was taken out and cooled to room temperature. The carbon nanotube-modified sodium dodecyl sulfate was slowly added to the stirred PUA. After stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0039] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 3.61×10 8 ohms / hq; the tensile strength is 49.436MPa, the elongation at break is 436.303%, the impact strength is 90.721% higher than that of pure aluminum sheet, and the adhesion to carbon steel is 8.297MP without primer.

[0040] Example 3 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was applied. After stirring evenly, the mixture was placed in a drying oven and dried. After drying, the mixture was cooled to room temperature for later use. Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain sodium dodecyl sulfate; wherein, in a molar ratio, the initial product of sodium dodecyl sulfate: n-butanol: saturated sodium carbonate solution = 53.2:106:1; Weigh 1.5 g of the stirred carbon nanotube (CNTs) mixture and 1 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cool them to room temperature for later use; 100g of PUA polyurea was placed in an oven for preheating. After sufficient preheating, it was taken out and cooled to room temperature. The carbon nanotube-modified sodium dodecyl sulfate was slowly added to the stirred PUA. After stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0041] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 8.34×10 7 ohms / hq; the tensile strength is 42.582MPa, the elongation at break is 736.303%, the impact strength is 96.721% higher than that of pure aluminum sheet, and the adhesion to carbon steel is 9.269MP without primer.

[0042] Example 4 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: (1) Place 1 g of carbon nanotubes (CNTs) and 5 g of KOH particles in a porcelain crucible, add 20 mL of distilled water, stir magnetically, and place in a drying oven to dry after stirring evenly. After drying, cool to room temperature for use; (2) Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; (3) taking the obtained sodium dodecyl sulfate out of the ice bath, placing it in a beaker containing crushed ice, adding 10 mL of n-butanol and stirring evenly, and then slowly adding 1 mL of saturated sodium carbonate aqueous solution to obtain sodium dodecyl sulfate; wherein, in a molar ratio, the initial product of sodium dodecyl sulfate: n-butanol: saturated sodium carbonate solution = 53.2:106:1; (4) Weighing 1 g of the stirred carbon nanotube (CNTs) mixture and 0.5 g of the sodium dodecyl sulfate mixture, placing them in an ice-water mixture container and stirring them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cooling them to room temperature for later use; (5) Preheat 100 g of PUA polyurea in an oven, take it out and cool it to room temperature after sufficient preheating, slowly add the carbon nanotube-modified sodium dodecyl sulfate into the stirred PUA, and stir evenly to obtain a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material.

[0043] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 6.85×10 8 ohms / hq; the tensile strength is 31.697MPa, the elongation at break is 465.389%, the impact strength is 76.721% higher than that of pure aluminum sheet, and the adhesion to carbon steel is 7.269MP without primer.

[0044] Example 5 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was applied. After stirring evenly, the mixture was placed in a drying oven and dried. After drying, the mixture was cooled to room temperature for later use. Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain sodium dodecyl sulfate; Weigh 2 g of the stirred carbon nanotube (CNTs) mixture and 1 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cool them to room temperature for later use; 100g of PUA polyurea was placed in an oven for preheating. After sufficient preheating, it was taken out and cooled to room temperature. The carbon nanotube-modified sodium dodecyl sulfate was slowly added to the stirred PUA. After stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0045] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 9.85×10 7 ohms / hq; the tensile strength is 37.697MPa, the elongation at break is 672.439%, the impact strength is increased by 101.332% compared with pure aluminum sheet, and the adhesion to carbon steel is 8.637MP without primer.

[0046] Example 6 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was applied. After stirring evenly, the mixture was placed in a drying oven and dried. After drying, the mixture was cooled to room temperature for later use. Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain sodium dodecyl sulfate; wherein, in a molar ratio, the initial product of sodium dodecyl sulfate: n-butanol: saturated sodium carbonate solution = 53.2:106:1; Weigh 2.5 g of the stirred carbon nanotube (CNTs) mixture and 1 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cool them to room temperature for later use; 100g of PUA polyurea was placed in an oven for preheating. After sufficient preheating, it was taken out and cooled to room temperature. The carbon nanotube-modified sodium dodecyl sulfate was slowly added to the stirred PUA. After stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0047] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 1.37×10 8 ohms / hq; the tensile strength is 34.773MPa, the elongation at break is 608.303%, the impact strength is 81.594% higher than that of pure aluminum sheet, and the adhesion to carbon steel is 9.324MP without primer.

[0048] Example 7 A method for preparing a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the process flow of which comprises the following steps: 1g carbon nanotubes (CNTs) and 5g KOH particles were placed in a porcelain crucible, 20mL distilled water was added, and magnetic stirring was applied. After stirring evenly, the mixture was placed in a drying oven and dried. After drying, the mixture was cooled to room temperature for later use. Place 3.5 mL of glacial acetic acid in a dry three-necked flask, cool it in an ice bath, add 1.5 mL of chlorosulfonic acid, and mix well. Slowly add 10 g of dodecanol in the form of a very fine solid powder to the cold acetic acid and chlorosulfonic acid over 5 minutes, and stir for 20 minutes until all the alcohol is dissolved and participates in the reaction; The obtained sodium dodecyl sulfate was taken out from the ice bath, placed in a beaker containing crushed ice, 10 mL of n-butanol was added and stirred evenly, and then 1 mL of saturated sodium carbonate aqueous solution was slowly added to obtain sodium dodecyl sulfate; wherein, in a molar ratio, the initial product of sodium dodecyl sulfate: n-butanol: saturated sodium carbonate solution = 53.2:106:1; Weigh 3 g of the stirred carbon nanotube (CNTs) mixture and 1 g of the sodium dodecyl sulfate mixture, place them in an ice-water mixture container and stir them thoroughly to obtain carbon nanotube-modified sodium dodecyl sulfate, and cool them to room temperature for later use; 100g of PUA polyurea was placed in an oven for preheating. After sufficient preheating, it was taken out and cooled to room temperature. The carbon nanotube-modified sodium dodecyl sulfate was slowly added to the stirred PUA. After stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material was obtained.

[0049] The resistance of the prepared carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 1.76×108 ohms / hq; the tensile strength is 32.589MPa, the elongation at break is 567.284%, the impact strength is 90.332% higher than that of pure aluminum sheet, and the adhesion to carbon steel is 9.562MP without primer.

[0050] Comparative Example 1 The same as Example 1, except that the carbon nanotubes and sodium dodecyl sulfate were directly mixed in a molar ratio of 1:1 to obtain a mixture of carbon nanotubes and sodium dodecyl sulfate, and then added to the PUA polyurea, the resistance of the polyurea composite material decreased severely by 7.75×10 11 ohms / hq, tensile strength is 20.39MPa, elongation at break is 395.314%, impact strength is not significantly improved compared with pure aluminum sheet, and adhesion to carbon steel is 4.562MPa without primer.

[0051] Comparative Example 2 The same as Example 1, except that after the PUA polyurea is preheated, it is not cooled to room temperature, and the carbon nanotube-modified sodium dodecyl sulfate antistatic agent is directly added to the preheated PUA polyurea and stirred evenly, then the resistance of the composite material is reduced to 3.89×10 9 ohms / hq, and the other mechanical properties also decreased slightly.

[0052] Comparative Example 3 The same as Example 1, except that sodium dodecylbenzene sulfonate is replaced by sodium dodecylsulfonate, and then obvious agglomeration occurs during the preparation of the modified polyurea coating, which eventually leads to failure of film formation. This is because the molecular weight of sodium dodecylbenzene sulfonate is too large, which will cause molecular entanglement within the modified coating system, which will increase the viscosity of the mixture during the mixing process and destroy the main chain structure of the polyurea.

[0053] Comparative Example 4 Same as Example 1, except that sodium dodecyl sulfate was replaced by sodium dodecyl sulfate, and the resistance of the composite material decreased significantly to 4.61×10 11 ohms / hq, tensile strength is 23.55MPa, elongation at break is 402.799%, and impact strength is not significantly improved compared to pure aluminum sheets. Without primer, adhesion to carbon steel is only 3.824MPa.

[0054] Comparative Example 5 The same as Example 1, except that there is no step (2) and step (3), and commercially available sodium dodecyl sulfate is used to replace the sodium dodecyl sulfate mixture, then the solubility and dispersibility during the reaction may be poor, and the generated product may not have been further optimized for surface modification. This indicates that although commercially available sodium dodecyl sulfate has a certain activity, the lack of additional solvent (such as n-butanol) and alkaline treatment (such as sodium carbonate solution) may cause its surface properties to be relatively rough, affecting the stability and dispersibility of the final product.

[0055] Comparative Example 6 Same as Example 1, except that, without step (1), the carbon nanotubes added directly in step (4) may result in the carbon nanotubes not being pretreated, and the surface properties may be relatively rough and the dispersibility is poor. This indicates that the pretreatment step (such as cooling in an ice bath and adding chemical reagents such as chlorosulfonic acid) is usually used to improve the surface activity and hydrophilicity of the carbon nanotubes, thereby improving their compatibility and dispersibility with other substances. If this step is skipped, the dispersibility of the carbon nanotubes may not be as good as that of the surface-modified samples, affecting the performance of the final product.

[0056] Comparative Example 7 The same as Example 1, except that in step (1), 5g of KOH is replaced by 5g of NaOH. Compared with the carbon nanotube mixture of the present invention, NaOH cannot provide surface activation ability, resulting in multiple obvious small block agglomerations during the preparation process, and the obtained polyurea composite material cannot be formed.

[0057] Test Example 1 A method for testing the antistatic properties of a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material comprises the following steps: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material obtained by the synthesis method in Example 1 was tested for resistance using a surface resistance tester, and the experimental data was recorded to analyze the antistatic properties of the material. The test environment was 50-55% RH and 25-27° C.

[0058] have Figure 1 The surface resistance curve of the sample shows that the surface resistance decreases first and then increases with the ratio of carbon nanotubes to modified sodium dodecyl sulfate. The smallest resistance is when the mass ratio of carbon nanotubes to sodium dodecyl sulfate is 2:1.3, and the resistance value is 3.85×10 7ohms / sq, and then the resistance increases with the increase of the mass ratio of carbon nanotubes to sodium dodecyl sulfate. This is because when the mass ratio is appropriate, the lipophilic group in the modified sodium dodecyl sulfate will be adsorbed on the surface of the material. After the impregnation is completed and dried, the hydrophilic groups in the antistatic agent molecules on the surface of the polymer material after the water is removed are arranged toward the air side, which is easy to absorb environmental moisture, or combine with moisture in the air through hydrogen bonds to form a monomolecular conductive layer, so that the generated static charge quickly leaks to achieve the purpose of antistatic.

[0059] Test Example 2 A tensile property test of a carbon nanotube modified sodium dodecyl sulfate-polyurea composite material comprises the following steps: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material obtained by the method in Example 1 was subjected to a tensile test using a tensile testing machine, and the experimental data were recorded to analyze the tensile strength and elongation at break of the material. The test was carried out at a strain rate of 50 mm / min, and at least three samples were tested according to ISO 37-2005. The tensile test piece was 35 mm long, 2 mm wide in the middle, 1 mm thick, and had a gauge length of 10 mm.

[0060] Depend on Figure 2 It can be seen that the tensile strength and elongation at break both increase first and then decrease with the ratio of the amount of carbon nanotubes added to the amount of dodecyl sulfonic acid added. When the mass ratio of the amount of carbon nanotubes added to the amount of dodecyl sulfonic acid added is 1:1, the tensile strength and elongation at break are both maximum values, 51.865MPa and 840.233%, respectively. This is because the carbon nanotube-modified sodium dodecyl sulfonate improves the mechanical properties of the polyurea coating while ensuring the antistatic properties of the material. The addition of carbon nanotubes can greatly enhance the flexible area of ​​the polyurea material.

[0061] Test Example 3 A test of the adhesion performance of a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material to a carbon steel substrate comprises the following steps: Adhesion test was performed using a pull-off adhesion tester (PosiTector® AT) from DeFelsko, USA. At least four samples were tested according to ASTM D4541. Before testing, ensure that the coating surface on the substrate is clean and free of contamination; stick a suitable size of ingot on the coating surface with a suitable adhesive to ensure that the adhesive is fully cured; record the maximum tensile force when the coating is separated, and observe and record the separation mode (such as coating self-destruction, separation of the coating and substrate interface, substrate damage, etc.).

[0062] Depend on Figure 3It can be seen that the adhesion of the carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material first increases and then decreases with the increase of the mass ratio of the carbon nanotubes added to the sodium dodecyl sulfate added. When the mass ratio of the carbon nanotubes added to the sodium dodecyl sulfate added is 1:1, the adhesion based on the carbon steel substrate is the largest, which is 10.797MPa. This is because the addition of modified sodium dodecyl sulfate makes the polyurea system contain more hydrogen bonds and improves the fluidity of the polyurea coating to a certain extent, so that the coating can better cover the surface of the substrate, thereby achieving a better adhesion effect.

Claims

1. A method for preparing a carbon nanotube-modified sodium dodecyl sulfate antistatic agent, characterized in that: The following steps are involved: S1: preparing a carbon nanotube mixture; The carbon nanotubes and KOH are mixed, distilled water is used as a solvent, and the mixture is stirred to react uniformly. After drying, the mixture is cooled to room temperature to obtain a carbon nanotube mixture. S2: preparing a sodium dodecyl sulfate mixture; (1) mixing the sufficiently cooled glacial acetic acid and chlorosulfonic acid uniformly, adding dodecanol, and stirring thoroughly until the dodecanol is completely dissolved to obtain a primary product of sodium dodecyl sulfonate; (2) placing the initial product of sodium dodecyl sulfate at low temperature, stirring it evenly with n-butanol, and slowly adding a saturated sodium carbonate aqueous solution to obtain a sodium dodecyl sulfate mixture; S3: Preparation of carbon nanotube modified sodium dodecyl sulfate antistatic agent; The carbon nanotube mixture and the sodium dodecyl sulfate mixture are placed in an ice-water mixture, fully stirred to obtain a carbon nanotube-modified sodium dodecyl sulfate antistatic agent, and then cooled to room temperature.

2. The method for preparing the carbon nanotube-modified sodium dodecyl sulfate antistatic agent according to claim 1, characterized in that: In the step S1, the mass ratio of carbon nanotubes to KOH is 1:(5-15); the stirring rate for uniform stirring reaction is 100-200 r / min, and the stirring time is 1-2 h.

3. The method for preparing the carbon nanotube-modified sodium dodecyl sulfate antistatic agent according to claim 1, characterized in that: In step S2 (1), the molar ratio of glacial acetic acid: chlorosulfonic acid: dodecanol is (2-3): 1: (1-2); the powder particle size of the dodecanol is 60-90 nm; in step S2 (2), the low-temperature reaction is carried out in an ice-water mixture; the molar ratio of sodium dodecyl sulfonate initial product: n-butanol: saturated sodium carbonate solution is (50-55): (105-110):

1.

4. The method for preparing the carbon nanotube-modified sodium dodecyl sulfate antistatic agent according to claim 1, characterized in that: In the step S3, the mass ratio of carbon nanotubes to sodium dodecyl sulfate is (2-3):(1-2).

5. A carbon nanotube modified sodium dodecyl sulfate antistatic agent, characterized in that: The method is prepared by any one of claims 1 to 4.

6. A carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, characterized in that: The invention comprises the carbon nanotube-modified sodium dodecyl sulfate antistatic agent as claimed in claim 4 and PUA polyurea.

7. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material according to claim 6, characterized in that: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material, the added mass ratio of PUA polyurea and carbon nanotube-modified sodium dodecyl sulfate antistatic agent depends on the completeness of the reaction, and the ratio of the number average molecular weight of the polyurea side chain to the number average molecular weight of the carbon nanotube-modified sodium dodecyl sulfate antistatic agent is (1.22~18.85):

1.

8. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material according to claim 6, characterized in that: The resistance range of the carbon nanotube modified sodium dodecyl sulfate-polyurea composite material is 3.85×10 7 ~6.85×10 8 ohms / hq, the tensile strength ranges from 31MPa to 52MPa, the elongation at break ranges from 436% to 841%, and the impact strength can be increased by 76% to 116% compared with pure aluminum sheets. Under primer-free conditions, the adhesion to carbon steel can reach 7 to 11MPa.

9. The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material according to claim 6, characterized in that: The carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material is prepared by the following preparation method: The PUA polyurea is preheated, and after being fully preheated, it is cooled to room temperature. With stirring, the carbon nanotube-modified sodium dodecyl sulfate antistatic agent is slowly added to the PUA polyurea, and after stirring evenly, a carbon nanotube-modified sodium dodecyl sulfate-polyurea composite material is obtained.

Citation Information

Patent Citations

  • Preparation of multi-wall carbon nano-tube / dodecyl sodium sulfonate / polyvinyl alcohol compound film

    CN101497701A

  • Carbon nano-tube modified TPU (thermoplastic polyurethane) antistatic film

    CN106084738A

  • Functionalized carbon nanotube nanocomposite membranes and methods of their fabrication

    WO2013170249A1